Improving the service of posyandu lansia (geriartri health service) at Sumbersuko and Pandanrejo Village, Sub-District Wagir, Malang, East Java - anisyah achmad; Ema Pristi Yunita; Sri Winarsih; Ratna Kurnia Illahi (Future Science, 2019)
The main purpose of Posyandu Lansia (Geriartri Health Service) is to monitor the health status of geriartri patients, and to improve their knowledge about health. Up to 20% of geriartri population usually utilizing the health service. This public service activity was conducted at sub village Kenongo Barat and Sumberpang Selatan (Sumbersuko village), and Pandansari and Ngingrim (Pandanrejo village). The health advocacy activity was including presentation by using leaflet and poster about hypertension and hypercholesterol. Health check-up was also performed, including monitoring blood pressure and blood cholesterol level. Geriartric patients also received healthy food during the activity. The result of health check-up showed that there were more cases of hypertension and hypercholesterol. 48.6% case of hypertension and 55.5% case of hypercholesterol were founded in Kenongo Barat. While in Sumberpang Selatan, Pandansari, and Ngringim there were 45.8%, 64.7%, and 63,5% cases of hypertension; and 22.9%, 51.4%, and 23% case of hypercholesterol respectively. Those results showed that more education are needed for these geriartri patients, especially about disease factors and disease prevention.